2005
DOI: 10.1002/app.22257
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of homogeneous membranes prepared from sulfonated poly(phenylene oxide)

Abstract: This article investigates the comprehensive properties of sulfonated poly(phenylene oxide) (SPPO) membranes with different sulfonation degrees and presents the completion of previous work necessary for the application of SPPO membranes to proton-exchange membrane fuel cells. The sulfonation level has been accurately determined by conductometric titration and 1 H-NMR, and the glasstransition temperature has been obtained with both differential scanning calorimetry and dynamic mechanical thermal analysis. Sulfon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…In the current work, we conduct a series of MD simulations over pure SPPO membranes to better understand their structural and dynamical behavior as a potential PEM and attain molecular level viewpoint. Since experimental observations from Guan et al [11] and Yang et al [12] about pure SPPO membranes suggested that the water uptake capacity of these acid-type PEMs is a more influential parameter on membrane performance, as observed in our more recent MD study of SPEEK membranes with different sulfonation levels [35], the present simulation work is directed toward the investigation of effect of membrane hydration level on microstructure and transport dynamics of pure SPPO membranes using MD simulation methods.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the current work, we conduct a series of MD simulations over pure SPPO membranes to better understand their structural and dynamical behavior as a potential PEM and attain molecular level viewpoint. Since experimental observations from Guan et al [11] and Yang et al [12] about pure SPPO membranes suggested that the water uptake capacity of these acid-type PEMs is a more influential parameter on membrane performance, as observed in our more recent MD study of SPEEK membranes with different sulfonation levels [35], the present simulation work is directed toward the investigation of effect of membrane hydration level on microstructure and transport dynamics of pure SPPO membranes using MD simulation methods.…”
Section: Introductionmentioning
confidence: 96%
“…They obtained the highest conductivity of 0.015 S/cm for 28.7% sulfonation level. Using atomic force microscopy (AFM) analysis, Guan et al observed well-connected ionic domains within the SPPO membranes at higher sulfonation levels which were attributed to greater water uptake in membrane with increased degree of sulfonation [11]. Yang et al reported proton conductivity values of 2.5 Â 10 À5 e1.2 Â 10 À2 S/cm for SPPO membranes with different degrees of sulfonation ranging from 9.8% to 40.1% [12].…”
Section: Introductionmentioning
confidence: 98%
“…Two new transmission peaks corresponding to the symmetric stretching band of aromatic -SO 3 H group and C-S stretching vibration were appeared at 1061 and 655 cm −1 , respectively, in sulphonated PMMA in figure 1a. 23 Figure 1b shows the hydroxyl group substituted PMMA FTIR spectrogram; a new broad peak was observed at and it subjected to -OH stretching, which reveals the presence of hydroxyl group in modified PMMA. Two new peaks appeared at 3330 and 3240 cm −1 in thiouronium chloride functionalized PMMA and these peaks are responsible for the N-H asymmetric and symmetric stretching, respectively.…”
Section: 3d Statisticsmentioning
confidence: 97%
“…It has been known that the asymmetrical stretching vibrations of sulfonic acid groups appear at $ 1180 cm À1 , but we could not readily observe it because of near overlapping absorbances. 18 However, it still can get conclusion that the sulfonic acid groups has been introduced into the polymer chains.…”
Section: Fourier Transform Infraredmentioning
confidence: 99%